An annotated catalogue of selected works for clarinet by South African composers - Webb, Clare Louise (College of Music, 2014)
The dissertation consists of an annotated catalogue of nineteen selected works for clarinet by South African composers. These are presented in chronological order, based on the year of composition. A short biographyof the composer is given before the work is discussed. Of the analysed works, all those for solo clarinet or for clarinet and piano have been graded. A thesis of a similar nature, written in 1989 by L.A. Hartshorne, entitled ""The Compositions for Clarinet by South African Composers"", contains details of twenty-four works written between 1928 and circa 1981. The majority of the compositions analysed in the current dissertation were written from around 1981 onwards, and to some extent, therefore, this research could be seen as complementary to the information contained in the aforementioned thesis. An addendum lists all the South African works featuring solo clarinet that the author was able to trace. These include solo works, cham ber works for up to nineteen instruments and concerto-type works with strings or orchestra.